Conceptualisation of reproduction and adaptive strategies in the constructivist perspective - Shevchik, Dominik O.; Nedelevskaya, Ilona G. (Journal of the Belarusian State University. Sociology, 2022)
The article highlights the relevance of finding new approaches in the conceptualisation of adaptive strategies. It is argued that the main approaches that have developed in the sociology of adaptations are characterised by two types of reductionism: one of them is associated with the primacy of objective structures over the subject, and the other with the primacy of the subject over objective structures. The article proposes a new conceptual scheme of social agents’ strategies for the reproduction of the field and adaptation in it through the theoretical resource of the language of P. Bourdieu’s structuralist constructivism. For this purpose the authors demonstrate the interrelation of such key categories as «structure», «field», «habitus», «illusio» and «doxa» in the conceptualisation of various strategies of agents with their typologisation. This step, according to the authors, gives the opportunity to avoid the two designated poles in the sociological conceptualisation of adaptations and to provide higher relevance of operationalisation of reproduction and adaptation strategies applicable for empirical research.